2022
DOI: 10.3390/pharmacy10010009
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Following Prolonged Use of Hand Hygiene Products: A Systematic Review

Abstract: Background: This systematic review aimed to establish whether antimicrobial resistance (AMR) occurs following prolonged use of antimicrobial hand hygiene (HH) products, and, if so, in what magnitude. Methods: Key bibliographic databases were searched to locate items on HH use and AMR development from database inception to December 2020. Records were screened and full texts of all potentially eligible articles were retrieved and checked for inclusion. The following data from the included studies were abstracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Also, a survey study of hand hygiene practices among Indian medical undergraduates revealed that only 27.6% of students had good knowledge of hand hygiene practices [ 32 ]. Though it has been newly hypothesised that the prolonged use of hand hygiene products may cause AMR in healthcare settings [ 33 ], proper hand hygiene is regarded as one of the most important infection control measures [ 34 , 35 ]. Hand hygiene is specifically referenced as a principal practice for the prevention and control of the dissemination of antibiotic resistance with proven effectiveness in the case of VRE transmission [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, a survey study of hand hygiene practices among Indian medical undergraduates revealed that only 27.6% of students had good knowledge of hand hygiene practices [ 32 ]. Though it has been newly hypothesised that the prolonged use of hand hygiene products may cause AMR in healthcare settings [ 33 ], proper hand hygiene is regarded as one of the most important infection control measures [ 34 , 35 ]. Hand hygiene is specifically referenced as a principal practice for the prevention and control of the dissemination of antibiotic resistance with proven effectiveness in the case of VRE transmission [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, COVID-19 is a viral disease, and only a few patients might have bacterial co-infections; therefore, the use of antibiotics is not always necessary [ 25 ]. COVID-19 has increased the worldwide usage of antibiotics, personal protective equipment, and personal care products, such as soaps, handwashing liquids, and alcohol-based hand sanitizers, causing a knock-on effect in the existing global AMR problem [ 26 , 27 , 28 , 29 , 30 ]. Furthermore, the patients in intensive care, on prolonged mechanical ventilation, and with ventilator-associated pneumonia could have contributed to the colonization with nosocomial pathogens and led to an improved number of resistant isolates [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…faecalis infection[17]. A systematic review of four studies suggested that the prolonged use of hand hygiene products may cause antimicrobial resistance (AMR) in health care settings[18].…”
mentioning
confidence: 99%